2014
DOI: 10.3823/749
|View full text |Cite
|
Sign up to set email alerts
|

Colistin in Critically Ill Patients: A Critical Review

Abstract: Colistin emerged in the last decade as a savior for the treatment of critically septic patients who suffer MDR-GNB infections. This development came in time with the drying new antibacterial pipelines. MDR-GNB became problematic in ICU's including MDR Acinetobacter spp., Pseudomonas aeruginosa, and carbapenemase-producing Enterobacteriaecae (CPE). With the resurgence of wide colistin prescription especially in ICU's, awareness on when to switch to this reintroduced drug is required. Recently, it is observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Colistin emerged in the last decade as a savior for the treatment of critically septic patients who suffer MDR-GNB infections [24]. It is frequently used as combination therapy in order to maximize killing effect of pathogens, reducing rate of resistance, optimizing clinical outcome, and reducing mortality [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colistin emerged in the last decade as a savior for the treatment of critically septic patients who suffer MDR-GNB infections [24]. It is frequently used as combination therapy in order to maximize killing effect of pathogens, reducing rate of resistance, optimizing clinical outcome, and reducing mortality [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently used as combination therapy in order to maximize killing effect of pathogens, reducing rate of resistance, optimizing clinical outcome, and reducing mortality [25]. However two earlier meta-analyses published in 2003 and 2004 in BMJ revealed that combination therapy did not change rates of fatality and increased adverse events [24]. …”
Section: Discussionmentioning
confidence: 99%
“…2 A large retrospective cohort study from 2000 to 2007 showed incidence rates as low as 10%. 11 The reason for the lower rates of nephrotoxicity may be due to the use of more purified preparations, better ICU monitoring and avoidance of the coadministration of other nephrotoxic drugs (e.g. the aminoglycosides and vancomycin).…”
Section: Adverse Effectsmentioning
confidence: 99%